2018
DOI: 10.1016/j.vetimm.2018.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Poly(ADP-ribose) Polymerase1 (PARP1) expression and activity in cells purified from blood and milk of dairy cattle

Abstract: Poly(ADP-ribosyl)ation (PAR) is a post-translational protein modification catalysed by enzyme member of the poly(ADP-ribose) polymerases (PARPs) family. The activation of several PARPs is triggered by DNA strand breakage and the main PARP enzyme involved in this process is PARP1. Besides its involvement in DNA repair, PARP1 is involved in several cellular processes including transcription, epigenetics, chromatin re-modelling as well as in the maintenance of genomic stability. Moreover, several studies in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Moreover, the characterization of milk cell populations showed that quarters with high SCC exhibit an increase in phagocytes (neutrophils and macrophages). Considering that macrophages are important players in the inflammatory response, we proposed that the high PAR level found in milk with high SCC could be connected to PARP-1 activation in the increased proportion of the macrophages population [9]. According to these findings, PAR could be considered as an inflammatory mediator produced by both lymphocytes and monocytes/macrophages.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, the characterization of milk cell populations showed that quarters with high SCC exhibit an increase in phagocytes (neutrophils and macrophages). Considering that macrophages are important players in the inflammatory response, we proposed that the high PAR level found in milk with high SCC could be connected to PARP-1 activation in the increased proportion of the macrophages population [9]. According to these findings, PAR could be considered as an inflammatory mediator produced by both lymphocytes and monocytes/macrophages.…”
Section: Discussionmentioning
confidence: 95%
“…Research on the involvement of PARP-1 in bovine intramammary infection is limited. We have recently reported that unhealthy udders with high SCC show changes in milk somatic cell composition and increased intracellular poly(ADP-ribose) levels [9]. More recently, we showed that the conventional flow cytometry analysis applied to milk samples is a useful tool to detect new immunological markers as potential indicators of udder health [10].…”
Section: Introductionmentioning
confidence: 99%
“…To assess the concentration of PAR, nuclear extracts were prepared from freshly collected PBMC samples. PAR quantification was conducted using the HT PARP in vitro Pharmacodynamic Assay II kit from Trevigen, following the manufacturer's protocol [ 36 ]. Chemiluminescent signals were recorded using the Victor X light plate reader from PerkinElmer Inc.…”
Section: Methodsmentioning
confidence: 99%